Wood mass-customized housing: A dual computer implementation design strategy - Kwiecinski, K. (2021)
This paper reports our current research on automatic generation of houses layouts according to future inhabitant's requirements. For that generation we propose the use of a design method based on shape grammars that encodes light wood frame construction guidelines. Two different implementations for the design system are presently under development. One based on shape grammars supplemented with procedural knowledge and another using a genetic algorithm. Both implementations allow the generation of house layouts that fulfill both the user requirements and the design language.